(untitled) (SAARC Journal of Agriculture, 2019)
The aim of this study was to know the commonly available medicinal plants and to document their usages. Study was carried out around periphery of ’Gyaneswor Community Forest’ of Bharatpur-16 of Chitwan district of Nepal. Altogether, forty household were selected by random sampling, and key informant interview was carried out with community forest personnel’s and leading farmers. Most of the respondents of Bharatpur-16 were found to be dependent on medicinal plants for their primary health care. Because of no side effect, easy availability and cost effectiveness of medicinal plants, most people were found satisfied using it. However, the use of and preference for medicinal plant was found limited to minor diseases only. The findings of this study revealed that there are many medicinal plants in our periphery that can be used as an alternative for allopathic medicines, but they need to be systematically managed and conserved. SAARC J. Agri., 16(2): 129-141 (2018